Exploring the Relationship Between Ethics and Trust in Human–Artificial Intelligence Teaming: A Mixed Methods Approach. (December 2022) - Textor, Claire; Zhang, Rui; Lopez, Jeremy; Schelble, Beau G.; McNeese, Nathan J.; Freeman, Guo; Pak, Richard; Tossell, Chad; de Visser, Ewart J.
Advancements and implementations of autonomous systems coincide with an increased concern for the ethical implications resulting from their use. This is increasingly relevant as autonomy fulfills teammate roles in contexts that demand ethical considerations. As AI teammates (ATs) enter these roles, research is needed to explore how an AT's ethics influences human trust. This current research presents two studies which explore how an AT's ethical or unethical behavior impacts trust in that teammate. In Study 1, participants responded to scenarios of an AT recommending actions which violated or abided by a set of ethical principles. The results suggest that ethicality perceptions and trust are influenced by ethical violations, but only ethicality depends on the type of ethical violation. Participants in Study 2 completed a focus group interview after performing a team task with a simulated AT that committed ethical violations and attempted to repair trust (apology or denial). The focus group responses suggest that ethical violations worsened perceptions of the AT and decreased trust, but it could still be trusted to perform tasks. The AT's apologies and denials did not repair damaged trust. The studies' findings suggest a nuanced relationship between trust and ethics and a need for further investigation into trust repair strategies following ethical violations.